2011
DOI: 10.1136/gut.2011.239301.492
|View full text |Cite
|
Sign up to set email alerts
|

Is histology required for the diagnosis of alcoholic hepatitis? a review of published randomised controlled trials

Abstract: IntroductionThe need for liver biopsy to diagnose alcoholic hepatitis (AH) in the clinical setting remains controversial. Coagulopathy and/or ascites may preclude percutaneous biopsy and facilities for transjugular biopsy are not universally available. Despite this, some experts still advocate that biopsy confi rmation of AH is a prerequisite for determining diagnosis, prognosis and treatment strategy for this condition. Aim The authors aimed to review the already published literature in the form of randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Other trials in this field 22,55 have required liver biopsy and histological confirmation of the diagnosis prior to inclusion; however, in the UK, the USA and much of Europe, liver biopsy is rarely performed for diagnostic confirmation and reserved only for diagnostic uncertainty. This strategy is vindicated by a number of studies 22,[55][56][57] that show that clinicians can accurately judge the diagnosis by the recent use of alcohol and also applying of strict criteria on the duration of jaundice. A trial requiring liver biopsy could not have recruited this number of subjects, as many centres do not have access to the transjugular technique that would be required in this group of patients or would have considered the procedure to be unethical.…”
Section: Discussionmentioning
confidence: 99%
“…Other trials in this field 22,55 have required liver biopsy and histological confirmation of the diagnosis prior to inclusion; however, in the UK, the USA and much of Europe, liver biopsy is rarely performed for diagnostic confirmation and reserved only for diagnostic uncertainty. This strategy is vindicated by a number of studies 22,[55][56][57] that show that clinicians can accurately judge the diagnosis by the recent use of alcohol and also applying of strict criteria on the duration of jaundice. A trial requiring liver biopsy could not have recruited this number of subjects, as many centres do not have access to the transjugular technique that would be required in this group of patients or would have considered the procedure to be unethical.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified that bilirubin of at least 5 Â ULN in the presence of ongoing alcohol use accurately differentiates SAH from decompensated cirrhosis [16]. In a review of randomized-controlled trials of therapy for SAH, bilirubin more than 80 mmol/l was associated with histological AH in 96% of patients [17]. Therefore, our criteria for the diagnosis of SAH were robust and evidence based.…”
Section: Methodsmentioning
confidence: 95%
“…In relation to use of widely published scoring systems such as modified DF, MELD and more recently GAHS [6,7], we agree that…”
Section: Clinicalmentioning
confidence: 95%
“…A recent review of all the randomised controlled trials of treatments for alcoholic hepatitis determined the accuracy of the clinical criteria used relative to subsequent histological confirmation. If only those studies, which used a minimum level of bilirubin (ranging from 80 to 100 lmol/ L) or whose patient population had a lower limit of bilirubin greater than 80 lmol/L, were considered, the accuracy of a clinical diagnosis rose to 96% [6]. This is very similar to a group of patients with ALD presenting with Acute-on-Chronic Liver Failure (ACLF) which has recent onset of hyperbilirubinaemia (>85 lmol/ L) as a major tenant of its definition [7].…”
Section: Is a Liver Biopsy Necessary In Alcoholic Hepatitis?mentioning
confidence: 99%